Preventing Malaria among Children in Zambia: The Role of Mother's Knowledge†. (12th August 2014) - Pylypchuk, Yuriy; Norton, Samuel W.
Abstract Malaria remains a devastating disease in Zambia, responsible for about 13% of deaths among children under age 5. Lack of malaria‐specific knowledge has been commonly assumed to be an important barrier to engagement in behaviors that prevent malaria. To the best of our knowledge, this is the first study that accounts for the endogeneity of maternal knowledge in household's ownership of insecticide‐treated nets (ITN), child's use of ITN, and household's protection against mosquitos (HSP). We account for the endogeneity of maternal knowledge through discrete factor and standard instrumental variable estimators. We find significant causal effects of maternal knowledge on the child's use of ITN and HSP but no significant effect on ownership of ITN. The causal effects of maternal knowledge on the use of ITN and HSP are strikingly larger in magnitude than the effects in the reduced form models. Copyright © 2014 John Wiley & Sons, Ltd.